The Response of Firms to Maternity Leave and Sickness Absence - Ian M. Schmutte; Meghan M. Skira (Global Labor Organization (GLO), 2022)
We study how firms respond to predictable, but uncertain, worker absences arising from maternity and non-work-related sickness leave. Using administrative data on over 1.5 million spells of leave in Brazil, we identify the short-run effects of a leave spell starting on firms' employment, hiring, and separations. Firms respond immediately by increasing hiring, but the increase is substantially less than one-for-one replacement. Hiring responses are more pronounced for absences arising in occupations with more transferable skills and in firms operating in thicker labor markets. Overall, our results imply that using external markets is costly and firms manage absences through other channels.
Keywords: J23; J21; J63; J68; J13; 330